Distinctive sequence patterns in metazoan and yeast nucleosomes: Implications for linker histone binding to AT-rich and methylated DNA - Cui, Feng (Oxford University Press, 2009)
Linker histones (LHs) bind to the DNA entry/exit points of nucleosomes and demonstrate preference for AT-rich DNA, although the recognized sequence patterns remain unknown. These patterns are expected to be more pronounced in metazoan nucleosomes with abundant LHs, compared to yeast nucleosomes with few LHs. To test this hypothesis, we compared the nucleosome core particle (NCP) sequences from chicken, Drosophila and yeast, extending them by the flanking sequences extracted from the genomes. We found that the known ∼10-bp periodic oscillation of AT-rich elements goes beyond the ends of yeast nucleosomes, but is distorted in metazoan sequences where the ‘out-of-phase’ AT-peaks appear at the NCP ends. The observed difference is likely to be associated with sequence-specific LH binding. We therefore propose a new structural model for LH binding to metazoan nucleosomes, postulating that the highly conserved nonpolar ‘wing’ region of the LH globular domain (tetrapeptide GVGA) recognizes AT-rich fragments through hydrophobic interactions with the thymine methyl groups. These interactions lead to DNA bending at the NCP ends and formation of a ‘stem-like’ structure. The same mechanism accounts for the high affinity of LH to methylated DNA—a feature critical for stabilization of the higher-order structure of chromatin and for repression of transcription.